The Impact of the COVID-19 Pandemic on Food Security and Food Sovereignty in Nunavut Communities ... - Horlick, Sidney A. (University of Alberta Library, 2021)
Background: For those living in regions already experiencing health and social difficulties, the COVID-19 pandemic and resulting policies to reduce spread have the potential to exacerbate existing issues, including increasing food insecurity in households. In Nunavut, where 70% of children are food insecure, many households rely on school breakfast or community food programs for nourishment (Egeland, 2011). As a result of the threat of the pandemic to the territory’s population, a variety of public health measures were enacted that may have impacted food security, including the closure of schools. Additional actions were taken, such as implementing emergency harvester support funding, to limit the impact of public health measures on household and community food security. The overall impact of these actions on community food sovereignty and security is not yet understood. Objectives: This research project has several inter-related objectives: a) Describe the measures in place to mitigate impacts of COVID-19 ...